Implementasi Pendekatan Saintifik dalam Kurikulum 2013 pada Mata Pelajaran Al-Qur`an Hadist di MAN I Sumbawa Besar - Sofiyandi, Muji Agus; Romelah , Romelah; Nurhakim, Muh. (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
The implementation of the scientific approach in Indonesia’s 2013 Curriculum is intended to promote student-centered learning, critical thinking, and meaningful knowledge construction, including in Islamic Religious Education. However, its application in Al-Qur’an Hadith learning still presents practical challenges, particularly in adapting scientific learning principles to religious subject matter. Previous studies have largely focused on normative descriptions of curriculum implementation, with limited attention to classroom-level dynamics and teacher strategies in specific local contexts. This study aims to analyze the implementation of the scientific approach in Al-Qur’an Hadith learning, identify the obstacles faced by teachers, and examine the efforts undertaken to address these challenges at MAN 1 Sumbawa Besar. This research employed a qualitative descriptive approach. Data were collected through classroom observations, semi-structured interviews with school leaders, teachers, and students, and documentation analysis of learning plans and instructional materials. The data were analyzed using qualitative techniques involving data reduction, data display, and conclusion drawing. The findings indicate that the scientific approach has been implemented through the stages of observing, questioning, collecting information, associating, and communicating. The approach contributes positively to student engagement and active learning. Nevertheless, several obstacles were identified, including limited instructional time, students’ low participation in questioning and communication stages, and variations in learning readiness. Teachers addressed these challenges through personal student approaches, improved lesson preparation, structured group work, and contextual learning strategies. This study contributes to the development of context-sensitive strategies for implementing the scientific approach in Islamic education. It concludes that successful implementation requires pedagogical flexibility, effective classroom management, and sustained support for teachers to optimize student participation and learning outcomes.